Sonata for cello and piano in C major, op. 102, no. 1 (Artaria edition, first issue) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Erdödy, Anna Mária grof, 1780?-1837 (dedicatee)::::::::::::::: (Artaria et Comp.; Vienna; Austria, 2023)
First Viennese edition of the Sonata for cello and piano in C major, op. 102, no. 1, first issue, lacking price on title page.